Pesticides in Stream Sediment and Aquatic Biota: Distribution, Trends, and Governing Factors - Survey, U. S. Geological (CRC Press, 2009)
More than 20 years after the ban of DDT and other organochlorine pesticides, pesticides continue to be detected in air, rain, soil, surface water, bed sediment, and aquatic and terrestrial biota throughout the world. Recent research suggests that low levels of some of these pesticides may have the potential to affect the development, reproduction, and behavior of fish and wildlife, and possibly humans.